The potentially neglected culprit of DC surface flashover: electron migration under temperature gradients - Chuanyang Li (Nature Portfolio, 2017)
Abstract This report intends to reveal the role of electron migration and its effects in triggering direct current (DC) surface flashover under temperature gradient conditions when using epoxy-based insulating composites. The surface potential and the surface flashover voltage are both measured using insulators that are bridged between two thermo-regulated electrodes. The space charge injection and migration properties under different temperature are detected. The results show that the surface potential rises significantly because of electron migration near the high voltage (HV) electrode under high temperature conditions, thus creating an “analogous ineffective region”. The expansion of this “analogous ineffective region” results in most of the voltage drop occurring near the ground electrode, which serves as an important factor triggering positive streamers across the insulation surface. This work is helpful in understanding of DC surface flashover mechanism from a new perspective and also has important significance in design of a suitable DC insulator to avoid surface flashover problem.